ASUHAN KEBIDANAN KOMPREHENSIF PADA NY. N DI PRAKTIK MANDIRI BIDAN Y KABUPATEN CIANJUR (Jurnal Kesehatan Siliwangi, 2023)
Pregnant women have right to get comprehensive care, quality, affordable, and have the right to decide about their pregnancy. Pregnancy, childbirth, puerperium, and newborn are physiological phases. Physiological condition must be still got good service, because it becomes life-threatening and even could lead of death. One of the ways that can be performed to reduce the mortality rate is conducting continuity of care. High risk detection of maternal and neonatal could be done by optimum continuity of care. The upbringing can involve various sectors to carry out of accompany of pregnant women as a promotional and preventive effort starting from the time when she is diagnosed as pregnant until the puerperium phase. The purpose of scientific paper is providing comprehensive care to client with a midwifery management approach. The case study is a method of research used, starting from the period of pregnancy, childbirth, postpartum, and newborns by involving a woman of 37 weeks gestation who is given continuity of care starting during pregnancy, childbirth, postpartum, and newborn in Cianjur Regency.  Client got excressive urine production, especially at night as a physiological problem during the third trimester of pregnancy. Client has been given the explanation about third trimester discomfort through counseling and also how to reduce discomfort and finally problem can be resolved. During the labor phase, puerperium, and newborns, there is no problem which is found. Continuity of care has been carried out allows the Client to undergo the period of pregnancy, childbirth, puerperium, and newborns normally, without any difficultie, and complication, as long as the client's problem can be resolved. Comprehensive midwifery care services will be carried out in accordance with the theory and standards of service as well as the rules and law of midwives so that there are no gaps during providing care.